2019
DOI: 10.1002/cam4.2366
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic body radiotherapy improves the survival of patients with oligometastatic non‐small cell lung cancer

Abstract: Purpose The aim of the study was to evaluate the efficacy and safety of stereotactic body radiotherapy (SBRT) for pulmonary lesions in oligometastatic non‐small cell lung cancer (NSCLC) patients, to explore prognostic factors of progression‐free survival (PFS) and overall survival (OS), to validate improved survival contributed by SBRT in oligometastatic NSCLC patients. Patients and methods A total of 71 oligometastatic NSCLC patients with 86 pulmonary lesions treated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…However, it was also reported that clinical and therapeutic characteristics such as KPS score, local therapy for BM, radiotherapy for primary lesion [18], subsequent treatment of Osimertinib [19], and diagnosed as oligometastasis [20] could influence OS. To eliminate the impact of potential confounders, and to further confirm metachronous BM was an independent prognostic factor of poorer OS, we performed multivariable Cox regression analysis to investigate the potential prognostic factors.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was also reported that clinical and therapeutic characteristics such as KPS score, local therapy for BM, radiotherapy for primary lesion [18], subsequent treatment of Osimertinib [19], and diagnosed as oligometastasis [20] could influence OS. To eliminate the impact of potential confounders, and to further confirm metachronous BM was an independent prognostic factor of poorer OS, we performed multivariable Cox regression analysis to investigate the potential prognostic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Comparisons of tumor volume, SUV max , TGIR, tumor necrosis rate, apoptosis rate, and Ki-67 + expression rate among groups and at different time points (mean ± S)Decreasing group (p > 0.05). The most obvious difference in apoptosis rates was observed on day 7 after radiation (t = 3.91, 2.93; p < 0.05).Figures 3,4; …”
mentioning
confidence: 89%
“…The radiotherapy model for malignancy has transformed from conventional fraction radiotherapy (CFRT) to hypofractionated radiotherapy, which is now considered to be a new and highly effective mode of radiation therapy [1,2]. Stereotactic body radiotherapy (SBRT) and stereotactic radiosurgery are common procedures in hypofractionated radiotherapy, especially SBRT, which is widely performed for lung cancer, colorectal cancer, liver cancer, and prostate cancer, and shows considerable improvement in the radiotherapeutic outcomes [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Hypo-fractionated radiotherapy (HFRT) includes stereotactic body radiation therapy (SBRT) and hypo-fractionated brachytherapy, both of which deliver a high biologically effective dose (BED) to the tumor while minimizing toxicity to the normal tissues. Therefore, HFRT can prompt superior local control and improved survival ( 2 ).…”
Section: Introductionmentioning
confidence: 99%